Estudo comparativo dos elementos do Balanço Hídrico Climatológico para cidades de São Paulo e para Paris - Comparative study of the elements of the climatic hydraulic balance for two cities of São Paulo State and Paris (Confins, 2019)
This paper presents the results of the application of the Gaussen (Bagnouls, Gaussen, 1962) methodology and the Climatological Water Balance (Thornthwaite, Mather, 1955) applied to the localities of Brazil (São Paulo and Piracicaba, SP) and Paris, France. The normal average data of climate attributes (temperature and precipitation) are worked. The results show that Gaussen 's methodology responds better in the classification of periods of the year of higher rainfall than those of lower rainfall or close to the numerical limit of the classification proposed by the authors.